Expressão imuno-histoquímica de cd133 em displasias epiteliais orais e carcinomas epidermoides orais - Luna, Ealber Carvalho Macedo (2015)
C ancer stem cells are a subpopulation of neoplastic cells, which have properties phenotypic differentiation, cell renewal and proliferation similar to normal stem cells are r esponsible for tumor support. Objective: To investigate the immunoreactivity of CD133, a marker of cancer stem cells in oral epithelial dysplasia and oral squamous cell carcinoma . Methods: 15 cases were selected as CEO and 15 cases of DEO, being held by immunohistochemistry by the streptavidin - biotin technique, usi ng anti - CD133 antibody (GTX60471, GeneTex®, San Antonio, TX, USA) with dilution of 1: 650 and antigen retrieval with citrate pH 6. the quantitative analysis was performed using the percentage of cells with positive immunostaining count in 5 fields at 4 00X magnification using the Imag e program J. the results were obtained and compared between groups through the Student t test and ANOVA followed by Bonferroni multifactorial post - test, based on the levels of significance of 5%. Results : Immunohistochemical eva luation showed positive staining in all cases the sample (100% of cases). In DEO group, it was observed that 77.6 ± 16.0 epithelial cells exhibited positive immunostaining for CD133 and CEO group was found that 82.6 ± 7.2 epithelial cells exhibited positiv e immunostaining for CD133; however, there was no statistically significant difference between groups (p = 0.283). Moreover, it was observed that, with respect to gender, anatomical location and degree of dysplasia, the positive staining was as follows: ma le (DEO: 76.4 ± 10.9 and CEO: 82.9 ± 6.3) (p = 0.526) and female ( DEO: 78.0 ± 17.9 and CEO: 82.1 ± 8.9) (p = 0588); tongue (DEO: 69.6 ± 23.2 and CEO: 83.5 ± 9.3) (p = 0.217), buccal mucosa (DEO: 84.8 ± 14.7 and CEO: 79.0 ± 5.7) (p = 0.618) and palate (DEO : 74.5 ± 6 .7 and CEO : 86.8 ± 10.3); mild DEO (78.0 ± 18.4), moderate DEO (72.7 ± 11.4) and DEO severe (80.1 ± 1.8) (p = 0899). However, there was no statistically significant difference between groups . Conclusion it is suggested that the presence of this cell subpopulation may not be essential for determining the malignant phenotype .